UJI EFEKTIVITAS EKSTRAK METANOL BUAH PARE (MOMORDICA CHARANTIA L.) TERHADAP PERTUMBUHAN ASPERGILLUS NIGER - Muhammad Ilham Gandi Ilham; Ika Dyah Kurniati Ika; Mega Pandu Arfiyanti Mega (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2022)
Aspergillus niger is a species of fungus from the genus Aspergillus which is reported to be the main cause of otomycosis. Bitter gourd (Momordica charantia L.) contains several compounds, namely phenols, flavonoids, triterpenoids, steroids, saponins, and alkaloids that have potential as antifungals. This study aims to determine the content of phytochemical compounds present in the methanol extract of bitter melon and to test the effectiveness of the methanol extract of bitter melon on the growth of Aspergillus niger through the MIC test. This study used an in vitro laboratory experimental research design with a post-test-only control group design method. The MIC test used the multilevel serial microdilution method which was observed visually. The extract concentrations used were 8000 µg/ml, 4000 µg/ml, 2000 µg/ml, 1000 µg/ml, 500 µg/ml, 250 µg/ml, 125 µg/ml, and 62.5 µg/ml. The fruit samples of this study was bitter gourd obtained from bitter gourd farmers in Bandungan District, Semarang Regency, and pure culture of Aspergillus niger FNCC 6018. Data analysis used descriptive analysis. The results of the phytochemical screening showed positive saponins, flavonoids, and phenolic compounds, and the MIC value was not found. It was concluded that the methanol extract of bitter melon was not effective in inhibiting the growth of Aspergillus niger.